Increasing Capacity in Processing Superior Local Products in Maron River Ecokarst - Wijayanti, Pipit; Setyawardhani, Dwi Ardiana; Rachman, Anung (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
According to information obtained from this community service activity, 80% people of Dersono Village work as farmers. The location of Dersono Village is within Gunungsewu Karst, which is known as a barren area. Therefore, it has been difficult for the villagers to get maximum harvests, which has impacted their economic standard of living. Being in the middle of the Karst area, Dersono Village has a potential that is the Maron River as it can be developed into a tourist attraction and become a source of the community's economy. In addition, Dersono Village has the potential with regard to their local commodities, namely coconuts, that can become superior products. The potential of this local coconut commodity can be developed as a superior processed product that can become a unique, distinctive souvenir and has more economic value rather than only selling the raw coconuts to collectors (intermediaries) or along the Maron River. To manage these existing potentials, adequate human resource skills are needed, one of which is through training in processing local products with economic value and activity in marketing processed local products. The training began with material delivery and continued with practices with the targeted community (PKK) to assess training achievement. A pre-test and post-test were administered on managing MSMEs, making and packaging coconut oil, and product marketing of blondo. The results were categorized on a scale of very low, low, medium, high, and very high understanding. The pre-test results showed 12.9% low, 48.4% medium, 35.5% high, and 3.2% very high. The post-test results showed significant differences, showing no low category, a decline in the moderate category to 16.1%, 61.3% for the high category, and 22.6% for the very high category. These results strongly suggest that there has been a significant improvement of the target community’s capacity after the training.